2002
DOI: 10.1046/j.1439-0531.2002.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pasture Nitrate Concentration and Concentrate Intake after Turnout on Embryo Growth and Viability in the Lactating Dairy Cow

Abstract: This study investigated the effects on embryo growth and survival rate of feeding heavily-fertilised spring grass, containing high levels of quickly-degradable nitrogen, to pregnant cows. Forty-eight lactating Holstein cows between 2 and 8 weeks pregnant were turned-out, after a one-week transition period onto high- or low-nitrate pasture and fed a high- or low-concentrate supplement. Cows grazing the High nitrate pasture had significantly higher milk and plasma urea concentrations than cows grazing the Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 2 publications
(1 reference statement)
1
7
0
1
Order By: Relevance
“…These field observations have been documented by several authors [6,9]. Corollary to this were reports in this study of neonatal and perinatal calf mortalities as well as low birth weights, reproductive failures, reduced lactation and hypothyroidism due to maternal chronic nitrate poisoning.…”
Section: Discussionsupporting
confidence: 81%
“…These field observations have been documented by several authors [6,9]. Corollary to this were reports in this study of neonatal and perinatal calf mortalities as well as low birth weights, reproductive failures, reduced lactation and hypothyroidism due to maternal chronic nitrate poisoning.…”
Section: Discussionsupporting
confidence: 81%
“…A high mean plasma urea concentration was associated with a significant reduction in pregnancy rate in dairy cows [ 59 , 60 ]. In contrast, high plasma urea concentrations due to high levels of dietary nitrogen had no effect on parameters of fertility in other studies [ 61 , 62 , 63 ]. Moreover, high blood urea and the metabolic indicators of NEB often occur simultaneously in high-yielding cows making it difficult to separate out any individual effects on subsequent fertility [ 58 ].…”
Section: Discussionmentioning
confidence: 71%
“…A more recent study examined the effects on embryo growth and viability in 48 cows between 2 and 8 weeks of gestation that were feeding on heavily fertilized grass containing high levels of nitrogen compared with those in control pasture (Laven et al 2002). No evidence was found that embryo survival or growth was affected from 20 days onward in pregnant cows grazing in either pasture.…”
Section: Reproductive Toxicitymentioning
confidence: 99%